MANTRA’s effect in raising pregnant women's awareness of cigarette smoke exposure’s impacts: a qualitative study - Zenina, Nafira (Borneo Scientific Publishing, 2025)
Anemia in pregnant women is a significant health problem because it has a direct impact on the mother and fetus, including increasing the risk of low birth weight, premature birth, and maternal and infant mortality. One risk factor that is often overlooked is exposure to cigarette smoke, especially from the household environment. Pregnant women in Klaseman Village, Sukoharjo, still face exposure to cigarette smoke from their home-smoking partners. Therefore, educational interventions are needed that can increase awareness among pregnant women to avoid exposure to cigarette smoke and prevent anemia. This study used a qualitative method to evaluate the effectiveness of the MANTRA educational media (MAri hiNdari Terpapar asap Rokok, cegah Anemia), namely leaflets containing information about the definition of anemia, symptoms, impacts, prevention methods, and the relationship between cigarette smoke exposure and the incidence of anemia. Empowerment activities were carried out on five pregnant women who attended the integrated health post through lectures, distribution of MANTRA, and interviews two weeks after education. The results showed an increase in knowledge of pregnant women regarding the dangers of cigarette smoke and changes in attitudes, such as moving away from sources of smoke, neutralizing the air in the house, and educating husbands not to smoke in the house. Evaluation using the Ottawa Charter approach showed that MANTRA successfully covered five elements of health promotion: supportive public policy, supportive environment, individual skill development, health service reorientation, and community action.